2009
DOI: 10.1080/00918360802551365
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging to the General and Lesbian Communities as Predictors of Depression Among Lesbians

Abstract: Research has indicated that a sense of belonging is important for mental health. This study investigated sense of belonging to the general community and sense of belonging to the lesbian community as predictors of depression among self-identified lesbians (n = 178). Participants completed the Psychological subscale of the Sense of Belonging Instrument and the Depression subscale of the Depression Anxiety Stress Scales. Results showed that although sense of belonging to the general community and sense of belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
62
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(65 citation statements)
references
References 23 publications
3
62
0
Order By: Relevance
“…This could be interpreted as gaining a sense of belonging from the general community rather than the Indigenous community. The positive effect caused by gaining a sense of belonging from the general community is supported by research concerning other marginalised groups (Hill, 2006;McLaren, 2009;Richmond and Ross, 2008). However, this research highlights the juxtaposition of gaining a sense of belonging from the general community when racism inhibits developing relationships with them and generates distrust towards them.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…This could be interpreted as gaining a sense of belonging from the general community rather than the Indigenous community. The positive effect caused by gaining a sense of belonging from the general community is supported by research concerning other marginalised groups (Hill, 2006;McLaren, 2009;Richmond and Ross, 2008). However, this research highlights the juxtaposition of gaining a sense of belonging from the general community when racism inhibits developing relationships with them and generates distrust towards them.…”
Section: Discussionmentioning
confidence: 56%
“…The social hierarchy that is perpetuated by these circumstances reinforces racial stigmas and creates a barrier to interactions. The detrimental effect of this barrier is emphasised in research regarding marginalised groups that indicates benefits of social support obtained via interactions with the wider community (McLaren, 2009;Richmond et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…33 Low sense of belonging to the lesbian community has also been associated with depression among self-identified lesbians. 34 To our knowledge, however, quantitative research has not previously investigated a potential relationship between LGBT community connectedness and mental health among nonmonosexual women specifically, although Frost and Meyer 19 report lower mean levels of LGBT community connectedness among the bisexual participants in their sample relative to gay/ lesbian participants. This is consistent with other qualitative research with bisexual people, which has identified biphobia within lesbian/gay communities as a significant barrier to LGBT community support for bisexual people.…”
Section: Discussionmentioning
confidence: 92%
“…Recent Australian research tested the applicability of four models to explain the interrelations between sense of belonging to the general community, sense of belonging to the lesbian and gay community and depression among adult lesbians (McLaren, 2009) and gay men (McLaren et al, 2008). First, results supported a direct effects model, with belonging to each community being associated with fewer depressive symptoms among gay men and lesbians.…”
mentioning
confidence: 96%
“…Low sense of belonging has been associated with low self-esteem, high levels of anxiety (Lee & Robbins, 1998), depression, and suicidal ideation (Bailey & McLaren, 2005), and fewer reasons to live (Kissane & McLaren, 2006). Low levels of sense of belonging to the general community have been associated with high levels of depressive symptoms among gay (McLaren, Jude, & McLachlan, 2008) and lesbian (McLaren, 2009) adults.…”
mentioning
confidence: 99%